Zachodnioeuropejski wzorzec gospodarczy a rozwój polskiego rolnictwa w świetle wybranej publicystyki Jana Lutosławskiego - Dajnowicz, Małgorzata (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
The articles of Jan Lutosławski, published in the first half of the 20th century, propagate West European patterns of development of Polish agriculture. Western industrial patterns should mainly be accepted by gentry who was responsible for the development of Polish farming. Lutosławski paid special attention to English patterns (as far as private ownership or attitude towards tradition are concerned), Danish patterns (when it comes to the development of education), German patterns (especially to the repair solutions of Little property). In the articles of Lutosławski one can also find justification for introducing the principles of national economy to Poland.